Effects of active alginate edible coating enriched with hydroxyapatite-quercetin complexes during the cold storage of fresh chicken fillets. (June 2022) - Malvano, Francesca; Montone, Angela Michela Immacolata; Capuano, Federico; Colletti, Chiara; Roveri, Norberto; Albanese, Donatella; Capparelli, Rosanna
Abstract: Alginate edible coatings enriched with quercetin glycosides and hydroxyapatite/quercetin complexes were evaluated as effective active coatings able to slow down the spoilage of fresh chicken fillets during the cold storage. Hydroxyapatite/quercetin complexes were preliminarily analysed by SEM, FTIR and zeta potential. Then alginate coatings were characterized for their ability to release quercetin in an aqueous medium which represents the base condition during the development of active edible food packaging. The microbiological parameters (total viable count, psychotropics bacteria count, Pseudomonas spp . and Enterobacteriaceae ), measured during the cold storage period at 6 °C, highlighted the capability of alginate coatings with hydroxyapatite/quercetin glucosides complexes to significantly inhibit the growth of spoilage bacteria, as well as the total volatile basic nitrogen during the cold storage period of 11 days. Likewise, the texture, colour and sensory parameters pointed out a positive effect of quercetin when complexed with hydroxyapatite to maintain the quality of fresh chicken fillet during the storage. Highlights: Alginate edible coatings with hydroxyapatite-quercetin complexes were developed. The release profile of quercetin from alginate coatings was studied. Hydroxyapatite-quercetin coatings were used for shelf life study of chicken fillets. Coatings with hydroxyapatite -quercetin inhibit the spoilage bacteria growth. The quality of chicken fillets was preserved for 11 days at 6 °C.